Pathogenic variants at the N-terminal arginine residue 44 disrupt human GABA transporter 1 function: insights from Drosophila epilepsy models - Shah, Nikita; Kasture, Ameya Sanjay; Kovalchuk, Vasylyna; Bjeletic, Lara; Hummel, Thomas; Sitte, Harald H.; Sucic, Sonja (Frontiers in Pharmacology, 2025)
Arginine 44 (R44) is a highly conserved residue in the human GABA transporter 1 (hGAT-1), a member of the solute carrier 6 (SLC6) family, which plays a critical role in regulating inhibitory neurotransmission in the central nervous system. To elucidate its functional importance, we characterized three epilepsy-associated pathogenic variants - R44Q, R44P and R44W - linked to myoclonic-atonic epilepsy (MAE) and developmental delay. Building on evidence that R44 resides within the N-terminal intracellular gate and is essential for transporter function, we employed biochemical, cellular and organismal models (HEK293 cells and Drosophila melanogaster, respectively) to assess the variants’ functional impairments, subcellular localization and trafficking. Particular emphasis was placed on R44Q, a validated variant with a pronounced clinical phenotype. The mutants trafficked to the plasma membrane, but were non-functional and exhibited reduced protein stability. In vivo, R44Q displayed cell-type–specific degradation: in astrocytes, GAT was rapidly cleared via proteasomal degradation, whereas in neurons, it showed lower expression with presynaptic enrichment. Proteasome inhibitors (MG-132, bortezomib) and the HDAC inhibitor trichostatin A (TSA) partially rescued R44Q function. Moreover, R44Q-expressing flies presented heat-induced seizures, which were mitigated by 4-phenylbutyrate (4-PBA) treatment. These findings elucidate the molecular basis of R44-mediated hGAT-1 dysfunction and highlight potential therapeutic avenues for SLC6A1-related neurodevelopmental disorders.